Comparative study of pre-operative CT scan and per-operative findings in carcinoma ovary - Naik, Reshika; R, Suchitra; Naik, Balakrishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Initial therapy for ovarian carcinoma involves aggressive surgery to remove as much tumor as possible. However, this procedure is not beneficial for patients unless tumor is optimally debulked. This study was performed to compare the CT scan findings and per-operative findings and to determine whether CT can be used to predict the success of debulking surgery. Methods: A retrospective and prospective study was conducted from 2011 to 2013 comparing pre operative CT scan findings and per operative findings of patients diagnosed with carcinoma ovary. 59 patients met the inclusion criteria. Five radiographic features were analysed and a score of 0 to 2 was assigned to each. These scores were added and compared to the surgical results. Results: We found that CT was highly sensitive in the diagnosis of retroperitoneal lymph node, ascites and omental involvement with sensitivity of 85.7%, 100% and 73.6% respectively. Sensitivity to detect peritoneal deposits and sub diaphragm deposits was 60% and 16.6% respectively. Specificity was uniformly greater than 85% for all parameters except ascites and retro peritoneal lymph nodes which was 71.4% and 54.8%. On a 10-point preoperative CT scoring system, a score of ≥3 identified patients whose tumors were not successfully debulked with a sensitivity of 79% and a specificity of 93%. Conclusions: CT scan is highly sensitive and specific in identifying metastatic disease and can be used as a pre-operative tool in advanced carcinoma ovary to guide further management.